2019
DOI: 10.1111/jcmm.14681
|View full text |Cite
|
Sign up to set email alerts
|

miR‐200c suppresses stemness and increases cellular sensitivity to trastuzumab in HER2+ breast cancer

Abstract: Resistance to trastuzumab remains a major obstacle in HER2‐overexpressing breast cancer treatment. miR‐200c is important for many functions in cancer stem cells (CSCs), including tumour recurrence, metastasis and resistance. We hypothesized that miR‐200c contributes to trastuzumab resistance and stemness maintenance in HER2‐overexpressing breast cancer. In this study, we used HER2‐positive SKBR3, HER2‐negative MCF‐7, and their CD44+CD24− phenotype mammospheres SKBR3‐S and MCF‐7‐S to verify. Our results demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…In addition, the inhibition of breast cell migration and invasion by trastuzumab was enhanced by miR-135b-5p agomir transfection. Tang et al (31) indicated that overexpression of miR-200c increased drug sensitivity to trastuzumab in HER-2-positive breast cancer cells, consistent with the data reported here. miR-135b-5p agomir enhanced the antitumor effect of trastuzumab in vivo and in vitro.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the inhibition of breast cell migration and invasion by trastuzumab was enhanced by miR-135b-5p agomir transfection. Tang et al (31) indicated that overexpression of miR-200c increased drug sensitivity to trastuzumab in HER-2-positive breast cancer cells, consistent with the data reported here. miR-135b-5p agomir enhanced the antitumor effect of trastuzumab in vivo and in vitro.…”
Section: Discussionsupporting
confidence: 91%
“…35 CD24, a sialoglycoprotein cell adhesion molecule that promotes adhesion and metastasis, was up-regulated in colon cancer patients with higher ST6GAL1 levels 36 and modulated chemosensitivity of breast cancer cells to 5-fluorouracil. 37 CD44 + CD24 − is a well-known surface marker for breast cancer stem cells responsible for tumor formation, infinite growth, recurrence, and metastasis, 38 suggesting an important role of CD24 in the breast cancer metastasis, chemosensitivity, and stemness.…”
Section: Discussionmentioning
confidence: 99%
“…The miR-200 family serves as tumor suppressors in a wide range of diseases and tumor entities, including breast cancer [ 32 , 52 ]. Numerous studies reported relevant roles for miR-200b and miR-200c in the inhibition of breast cancer initiation and progression of cancer via suppression of pivotal oncogenic functions and mechanisms, namely the EMT program, metastasis, cancer stem cell phenotype, and chemoresistance [ 52 , 53 , 54 , 55 , 56 , 57 ]. Apart from the tumor-suppressive role of the miR-200 family, other studies proposed that overexpression of miR-200s promotes the proliferative potential and metastatic capacity of transformed mammary epithelial cells [ 58 ].…”
Section: Discussionmentioning
confidence: 99%